Peran Rumah Sakit Terhadap Pecandu Narkotika Dalam Rehabilitasi Medis - Dila Puspita Dewi (Badan Penerbit STIEPARI Press, 2022)
The reasons for the use of narcotics due to heavy work, socio-economic abilities, and environmental pressures from co-workers are the trigger factors for narcotics abuse in the worker group. Rehabilitation programs are needed to free addicts from narcotics dependence so that the responsibility of medical rehabilitation institutions against narcotics abuse is very necessary. The formulation of the problem in this study is how is the responsibility of Bhayangkara Hospital Semarang towards members of the Police who are addicted to narcotics abuse in medical rehabilitation? The author uses a juridical and empirical approach. Data analysis used descriptive qualitative analysis. The results showed that: 1) Hospital responsibilities in the medical rehabilitation process include assessment, preparation of rehabilitation plans, outpatient or inpatient rehabilitation programs and post-rehabilitation programs. Hospitalization is in accordance with the rehabilitation plan that has been prepared taking into account the results of the assessment which includes medical intervention. 2) Obstacles in the implementation of rehabilitation are poor behavior, dealers or dealers are not necessarily users (pure dealers), lack of medical personnel, inadequate facilities, poor coordination in the security sector between the police and the rehabilitation center so that if it occurs conflicts between residents and the presence of residents who make a fuss, the rehabilitation center has difficulty in overcoming these problems. The solution to the problems above is to reorganize the behavior of addicts with regular monitoring, further investigation and investigation are needed to find out whether they are dealers or just users (addicts), adding medical personnel, adding facilities for rehabilitation homes, improving conditions between the police and rehabilitation centers. in this case Bhayangkara Hospital.